The Influence of Multimedia-Interactive Project-Based Learning Models on The Metacognitive Abilities, Critical Thinking Abilities and Fiber Optic Communication Learning Outcomes - Amalia, Dina; Hanafi, Ivan; Taryudi (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Critical thinking as a component in the high-level thinking process uses the basis of analyzing arguments and generating insight into each meaning and interpretation to develop cohesive and logical reasoning patterns. This research used quantitative research methods and aimed to determine the metacognitive abilities, critical thinking abilities, and learning outcomes of students before and after being treated through posttest pretest with control class and experimental class, so the research method used by researchers is quasi experimental. The research design used is Nonequivalent Control Group Design. The results of the pre-test statistical hypothesis test show that the significance value obtained in the independent sample t-test shows a significance value of 0.767 or in other words the significance value is greater than the alpha degree of 5% ( 0.767 > 0.05) so it can be said that there is no real difference in the average value of learning outcomes of XI SMK Telkom Jakarta between the experimental group and the control group.